A Strain of Bacillus amyloliquefaciens Can Prevent Vibrio vulnificus Colonization in Crassostrea gigas Oysters - Andrea Martha Freire-Peñaherrera; Ana Tirapé; Jerry Landívar-Zambrano; Juan Manuel Cevallos-Cevallos; Juan Manuel Cevallos-Cevallos (Frontiers in Marine Science, 2020)
The pathogen Vibrio vulnificus has been associated with the majority of clinical cases of septicemia and deaths attributed to shellfish consumption. However, reports on biocontrol agents against this pathogen are scarce. In this study, the strain A5 of Bacillus amyloliquefaciens (A5) was evaluated against V. vulnificus. The sensitivity of V. vulnificus to A5 was first assessed in vitro using selected solid media as well as autoclaved oysters (Crassostrea gigas). Then, the ability of A5 to colonize live oysters was evaluated, and the biocontrol efficacy was investigated in vivo using oysters inoculated with V. vulnificus before or after inoculation with A5. The survival of the pathogen in oysters was evaluated after 2, 3, 4, and 6 days of exposure to A5 in all the experiments. In vitro, A5 showed inhibition halos of 18 mm against V. vulnificus. In autoclaved oysters, A5 caused a significant reduction in the levels of V. vulnificus on day 2 at 5.14 log CFU/g, but the pathogen’s counts were restored after day 3. In vivo, A5 was able to survive in live oysters and prevented the colonization of V. vulnificus only when the biocontrol agent was inoculated before the pathogen. Results show the potential of A5 to prevent V. vulnificus uptake by oysters when administered prior to the pathogen.